PENGARUH DISIPLIN PREVENTIF DAN MOTIVASI EKTRINSIK TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. NATURA INDOLAND - Ayu Puspitasari; Wawan Prahiawan (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study was conducted to investigate the effect of preventive discipline and extrinsic motivation on employee performance through job satisfaction as an intervening variable.This study uses a quantitative research in accordance with questionnaires and surveys. Engineering samples of data collection using sample saturated with 61 respondents. The analytical method used in this research is multiple linear regression. SPSS version 20 is a program used in the process and research.The results show that the preventive discipline no positive effect on job satisfaction. T indicated by the results of arithmetic <T table (-0905 <1.671), so that H1 is rejected. Partially, extrinsic motivation positive effect on job satisfaction. T indicated by the results of arithmetic> T table (5,008> 1,671), so that H1 is accepted. Partially preventive discipline and significant positive effect on employee performance. This is shown by the results of T arithmetic> T table (4,746> 1,671), so that H1 is accepted. Partially, extrinsic motivation is not a positive and significant influence on employee performance. T indicated by the results of arithmetic <T table (-0138 <1.672), so that H1 is rejected. Partially, job satisfaction does not affect positively on employee performance. This is shown by the results of T arithmetic < T table (-0042 <1.672), so that H1 is rejected.Keywords: Preventive Discipline, Extrinsic Motivation, Job Satisfaction, Employee Performance